2004
DOI: 10.1029/2002jc001702
|View full text |Cite
|
Sign up to set email alerts
|

Vertical mixing schemes in the coastal ocean: Comparison of the level 2.5 Mellor‐Yamada scheme with an enhanced version of the K profile parameterization

Abstract: [1] The performance of two vertical mixing parameterizations in idealized continental shelf settings is analyzed to assess in what aspects and under what conditions they differ. The level 2.5 Mellor-Yamada turbulence closure (M-Y) is compared with an enhanced version of the K profile parameterization (KPP), which has been appended to include a representation of the bottom boundary layer. The two schemes are compared in winddriven one-and two-dimensional shallow ocean settings to examine differences in (1) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(76 citation statements)
references
References 25 publications
2
73
0
1
Order By: Relevance
“…MY performed similar to NN and better than GLS when the simulations were stable and completed. LMD mixed too much, which was also found for weak stratification by Durski et al (2004). They also found that MY mixed more than LMD in strong stratification and less in weak stratification.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…MY performed similar to NN and better than GLS when the simulations were stable and completed. LMD mixed too much, which was also found for weak stratification by Durski et al (2004). They also found that MY mixed more than LMD in strong stratification and less in weak stratification.…”
Section: Discussionmentioning
confidence: 79%
“…Although Durski et al (2004) investigated the performance of MY and LMD in ROMS, a comparison was not made of the performance of the new GLS scheme. Burchard and Bolding (2001) investigated several flavors of GLS, but not specifically for ROMS.…”
Section: Introductionmentioning
confidence: 99%
“…Although this parametrisation is widely used in coastal ocean application, it should be noted that the choice of turbulence closure scheme can have an impact on resulting circulation, especially in areas close to the shore. However, this impact seems negligible in the bottom layer of the sea (Durski et al 2004). On the whole, the physical assumptions made in this approach seem reasonable for the studied area and rather do not induce significant errors of modelled quantities.…”
Section: Uncertainties In Modellingmentioning
confidence: 99%
“…Modeling tools, with appropriate horizontal and vertical discretization, are needed (finite difference -finite volumes -finite elements; structured -unstructured grids). Also the choice in numerical parameterization schemes, particularly concerning vertical mixing, play a central role (Durski et al, 2004).…”
Section: W J Mckiver Et Al: Vertical Hydrodynamic Coastal Processesmentioning
confidence: 99%